DETERMINAN PRODUKSI CABAI MERAH DI KABUPATEN BANGKA TENGAH - Rati Purwasih; Novyandra Ilham Bahtera; Yulia Yulia (Universitas Sebelas Maret, 2020)
In Central Bangka, the productivity of red chili pepper remains at a low level, therefore it is necessary to increase the productivity. This study aims to analyze factors that influenced the production of red chili pepper in Central Bangka district. The study was conducted in Central Bangka District in four villages, namely Belilik, Sungkap, Keretak, and Trubus. The four villages were selected as the location of the study as the villages were the location of the national agriculture development of red chili pepper. This study used 40 red chili pepper farmers through simple random sampling. Ordinary Least Square was used to determine the factors affected the red chili pepper production in Central Bangka. The results showed that an increase in land area, use of fungicide and the correct use of recommended seed could improve the red chili pepper production. On the other hand, the increase use of the phosphorus fertilizer could decrease the production of red chili pepper. This study also found that the most responsive factor in increasing the production of red chili pepper was size of land.